Health Impacts of Yoga: A Brief Review - Ansori, Arif Nur Muhammad (Generasi Biologi Indonesia, 2023)
Yoga is a holistic practice that has been used for thousands of years to promote health and well-being. The physical postures, breath control, and meditation techniques used in yoga have been found to have numerous health benefits, including improving flexibility, strength, balance, and cardiovascular health, reducing stress and anxiety, and improving mental clarity and focus. Recent research has shown that yoga can also be an effective complementary therapy for a variety of health conditions, such as chronic pain, depression, anxiety, and insomnia. Yoga has been found to be particularly effective in reducing stress and anxiety, which are common risk factors for many chronic diseases. Yoga is a non-competitive practice that can be adapted to suit the needs and abilities of individuals of all ages and fitness levels. It is a safe and effective way to improve overall health and well-being, and can be easily integrated into a daily routine. Therefore, yoga is a valuable tool for promoting health and well-being on all levels - physical, mental, emotional, and spiritual. It has become increasingly popular around the world, and is now widely recognized as a valuable complementary therapy for a variety of health conditions.